Selected documents of the international petroleum industry 1975/76 - Organization of the petroleum exporting countries Vienna (Vienna : The Organization of the Petroleum Exporting Countries, 1977)
This volume the thirteenth in the series relates to the years 1975 and 1976. It covers important developments leading to a further consolidation of OPEC member Countries' control over their hydrocarbon resources.
Includes bibliographical references
hza 30/01/2019
Loans
Keywords: Petroleum industry; Oil and gas; Vienna